Mapping of Risk Areas Associated with Karst in Urban Area of the Municipality of João Pessoa-PB - Santos, Caio Lima; Silva, Osvaldo Girão; Vital, Saulo Roberto Oliveira (Sociedade & Natureza, 2022)
The city of João Pessoa has relief features formed by karstic processes, called closed depressions. The natural dynamics of the karst relief is dominated by the process of dissolution of rocks, especially carbonates. The geological characteristics identified, and the conditions related to the evolution of the relief in the city place it in an area susceptible to the occurrence of karst processes, which adds to the strong urbanization process observed in the area. Thus, this article aimed to identify and characterize landforms developed by karstification processes to enable the analysis of risks in these environments, considering, in addition to natural susceptibility, aspects related to forms of urban uses and occupation. For this purpose, we mapped features of karst relief, called closed depressions. A map of susceptibility to karstification processes was created by using the map algebra technique, considering the factors of structural conditions, lithology, and geomorphology, as well as the conditions of urban occupation. Finally, the generated data were superimposed producing the classification of risk areas associated with karstic processes. The structural condition has been found to represent the preponderant factor for the risk conditions in the city of João Pessoa, Paraíba state, in addition to the impacts introduced in the karst system due to human activities, which sometimes represent the trigger for the occurrence of phenomena such as the opening of craters in urban areas.